2019
DOI: 10.1111/1750-3841.14508
|View full text |Cite
|
Sign up to set email alerts
|

Solid Self‐Emulsifying Delivery System (S‐SEDS) of Dihydromyricetin: A New Way for Preparing Functional Food

Abstract: The present study was aimed at formulating and evaluating a novel solid self-emulsifying delivery system (S-SEDS) for the application in functional foods of dihydromyricetin (DMY). First, solubility study and pseudo-ternary phase diagram analysis were adopted to optimize the formulation of liquid self-emulsifying delivery system (L-SEDS). And the thermodynamic stable L-SEDS with 5% content of DMY was fabricated and further developed into a solid form via vacuum rotary evaporation with Aerosil 300 as the solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…17 The HR and CI no more than 1.25 and 21, respectively, prove that the powders have good flowability and are applicable to industrial production. 26 The angle of repose, HR and CI of BC/SE-OPEO are listed in Table 4. The results of the three parameters all conform to the above demands and as such it is considered that the prepared BC/SE-OPEO possesses good fluidity.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 99%
“…17 The HR and CI no more than 1.25 and 21, respectively, prove that the powders have good flowability and are applicable to industrial production. 26 The angle of repose, HR and CI of BC/SE-OPEO are listed in Table 4. The results of the three parameters all conform to the above demands and as such it is considered that the prepared BC/SE-OPEO possesses good fluidity.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 99%
“…Self-emulsifying formulation, composed of an oil, a surfactant, and a cosolvent, was easily produced on a large scale and exhibited a high carrying capacity, which resulted in an enhanced bioavailability and efficacy for the active substances. As an example, Wang et al [ 6 ] prepared a solid self-emulsifying system for the delivery of dihydromyricetin, which allowed them to overcome the poor water solubility and short biological half-life of this substance, thereby improving its antioxidant performance and bioavailability and providing a feasible solution for its application in foods and beverages. In addition, Pickering emulsions have been used to encapsulate flavor compounds to hinder their volatilization and oxidative degradation whilst also promoting their effective dispersion into commodities to achieve continuous aroma release [ 7 ].…”
Section: Applications On the Dispersed-phase Scalementioning
confidence: 99%
“…Then DHM-loaded solid self-microemulsion (DHM/S-SEDS) was prepared by adsorbing DHM/L-SEDS onto the solid adsorbent Aerosil 300. In vitro and in vivo experiments showed that DHM/S-SEDS improved the antioxidant activity and bioavailability of DHM, and showed good fluidity and stability under various storage conditions within 10 weeks (Wang et al., 2019 ). Theoretically, the increase in the specific surface area, the number of voids, and the depth of pores in the particle may lead to the difficulty of drug dissolution and the spontaneous aggregation of drug molecules (i.e.…”
Section: Pharmaceutical Designs Of Dhmmentioning
confidence: 99%